Suboccipital Decompression for Occipital Neuralgia - Andrea Trescot; Gabor Racz; Laszlo Nagy (Journal of Spine and Neuroscience, 2017)
Cervicogenic headaches are a significant cause of head and neck pain, and occipital neuralgia is a common component of these cervicogenic headaches. Occipital injections are commonly performed at the occipital ridge, but this site does not address more proximal entrapments of the nerve in the suboccipital region. Because of the potentially dangerous structures in this region, clinicians have tended to avoid the suboccipital region, despite the pathologies seen in this region. This article discusses the pathology of the region, the alternative techniques, and the novel interventional approach developed for this region, specifically the “Stealth” approach of occipital decompression.
Keywords: occipital neuralgia